Three views on the Rapture pre-, mid-, or post-tribulation? (Grand Rapids, MI Zondervan, 1996)
Contents: A history of the development of the rapture positions / Richard R. Reiter; The case for the pretribulation rapture position / Paul D. Feinberg with reponses by Douglas J. Moo and Gleason L. Archer; The case for the mid-seventieth-week rapture position / Gleason L. Archer with responses by Paul D. Feinberg and Douglas J. Moo; The case for the postribulation rapture position / Douglas J. Moo with responses by Gleason L. Archer and Paul D. Feinberg
First edition published 1984
Keywords: Rapture (Christian eschatology).; Tribulation (Christian eschatology).